On the Crisis of Silicon Valley Banks: Management Failures and Regulatory and Supervisory Deficiencies in Commercial Banking - Vilariño Sanz, Ángel (Papeles de Europa, 2024)
The article reports on the episode suffered by Silicon Valley Bank and the systemic impacts generated by the world banking system. Changes in the regulation of commercial banks in the so-called Basel III regulations are analyzed, as a result of the great financial crisis and the existing difficulties in measuring the risks that banks are exposed to, especially in the case of credit risks. and liquidity. Finally, the accent is placed on the importance of supervision and its great difficulties, taking into account not only the theoretical difficulties but also the political difficulties.